Genetic analysis of F2 Indian mustard (Brassica juncea L) lines for drought tolerance (Journal of Oilseed Brassica, 2026)
The genetics of morphological and biochemical determinants of drought tolerance in sixteen genotypes and their F2 population was investigated. Analysis of variance revealed significant differences among parents and F2 population for all the traits recorded in both E1 and E2. Estimates of genetic parameters for traits viz., main shoot length, number of siliquae per plant for E1 and days to 50% flowering, number of secondary branches for E2 environments were found to have high heritability coupled with high genetic advance. Estimates of genetic parameters from the pooled data of the environments also revealed that traits like plant height, main shoot length and number of siliquae per plant have high heritability coupled with high genetic advance thereby, indicating effectiveness of these traits in selection. Estimation of proline content in leaves at flowering stage was analysed to evaluatethe maximum stress tolerant cross combinations. Similarly, results for Drought Susceptibility Index (DSI) revealed that parents RB-77, RB-24, RB-69 and cross combinations DRMR-4006 x RB-24 followed by PM-25 x RB-24 and RH-749 x PM-25were found to be tolerant. Hence, these lines may be used for further improvement of draught tolerance breeding program in Oilseed Brassica.